Immunohistochemical Distinguishing between Canine Peripheral Nerve Sheath Tumors and Perivascular Wall Tumors - Vučićević Ivana (Sciendo, 2019)
Peripheral nerve sheath tumors (PNSTs) comprise a heterogeneous group of neoplasms originating from the elements of the nerve sheath. They are divided into two forms: benign and malignant PNST. Both benign and malignant PNSTs are not very common in domestic animals but they are reported in different animal species. Histologically, PNSTs are composed predominantly of spindle cells arranged in bundles, whorls and sheets, with a different number of pleomorphic cells and mitotic figures.